Awakenings art in society in Asia 1960s-1990s - Yu Jin, Seng; Katsuo, Suzuki (The National Museum of Modern Art, 2018)
A collaborative project which adopts a transnational framework to compare the crucial point when modern art transitioned to contemporary art across Asia. Aptly, this exhibition is co-curated by the National Museum of Modern Art, Tokyo; National Museum of Modern and Contemporary Art, Korea; and National Gallery Singapore, representing a continuity from earlier collaborative regional exhibitions such as Cubism in Asia: Unbound Dialogue (2005-2006, organised by the same three museums) and Realism in Asian Art (2010, organised by the Korean and Singaporean national museums).